Multi-Frequency Higher-Order ADI-FDTD Solvers for Signal Integrity Predictions and Interference Modeling in General EMC Applications - Kantartzis, Nikolaos V. (Applied Computational Electromagnetics Society Journal (ACES), 2022)
The precise and wideband modeling of electromagnetic interferences and their effect on the signal integrity of microwave structures is presented in this paper, via an efficient 3-D dispersionoptimized method. Introducing a novel frequencydependent alternating-direction implicit finitedifference time-domain algorithm in general curvilinear coordinates, the technique establishes a consistent multi-frequency higher-order stencil management formulation. Moreover, for arbitrary geometric discontinuities and abrupt curvatures, a field projection scheme is devised. Thus, the detrimental dispersion errors of existing approaches are drastically minimized and time-steps can now greatly exceed the stability condition at any frequency range. The proposed method leads to affordable simulations and very accurate results, as proven by a variety of electromagnetic compatibility problems.